2023
DOI: 10.3390/nano13172477
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Synapse Emulated by Indium Tin Oxide/SiN/TaN Resistive Switching Device for Neuromorphic System

Dongyeol Ju,
Sunghun Kim,
Sungjun Kim

Abstract: In this paper, we fabricate an ITO/SiN/TaN memristor device and analyze its electrical characteristics for a neuromorphic system. The device structure and chemical properties are investigated using transmission electron microscopy and X-ray photoelectron spectroscopy. Uniform bipolar switching is achieved through DC sweep under a compliance current of 5 mA. Also, the analog reset phenomenon is observed by modulating the reset voltage for long-term memory. Additionally, short-term memory characteristics are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Short-term memory (STM) is a part of the biological brain's memory, which performs critical functions such as fast response and information filtering [4]. Under minor stimuli, a previous study reported the existence of STM, which may be due to the partial formation of conductive filament [55]. Similarly, the STM of ITO/IGZO/TaN was investigated with Next, the short-term synapse characteristic of ITO/IGZO/TaN was tested.…”
Section: Synaptic Functions Of Igzo-based Memristormentioning
confidence: 99%
“…Short-term memory (STM) is a part of the biological brain's memory, which performs critical functions such as fast response and information filtering [4]. Under minor stimuli, a previous study reported the existence of STM, which may be due to the partial formation of conductive filament [55]. Similarly, the STM of ITO/IGZO/TaN was investigated with Next, the short-term synapse characteristic of ITO/IGZO/TaN was tested.…”
Section: Synaptic Functions Of Igzo-based Memristormentioning
confidence: 99%
“…Over the past few years, resistive switching memory has gained immense popularity within the scientific community owing to its excellent nonvolatility, high endurance, long retention time, fast switching speed, low power consumption, excellent down scalability, and high-density data storage capability, providing a feasible and cost-effective alternative to the existing silicon-based memory devices. Conventional memory devices, which are mainly based on silicon, have several limitations such as downscaling, high power consumption, heat death, etc . Moreover, performance enhancement of these devices has become excessively difficult in recent times .…”
Section: Introductionmentioning
confidence: 99%